2019
DOI: 10.1038/s41598-019-50988-2
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid receptor α as a novel contributor to adrenal cortex structure and function through interactions with Wnt and Vegfa signalling

Abstract: Primary aldosteronism (PA) is the most frequent form of secondary arterial hypertension. Mutations in different genes increase aldosterone production in PA, but additional mechanisms may contribute to increased cell proliferation and aldosterone producing adenoma (APA) development. We performed transcriptome analysis in APA and identified retinoic acid receptor alpha (RARα) signaling as a central molecular network involved in nodule formation. To understand how RARα modulates adrenal structure and function, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 86 publications
(95 reference statements)
1
9
0
Order By: Relevance
“…56 In addition, alterations in the retinoic acid pathway have also been linked recently to benign adrenocortical tumours secreting aldosterone. 57 In conclusion, our results offer human genetic evidence for the importance of the druggable RA pathway in ACC onset and extend its relevance to progression of both paediatric and adult ACC. These findings will impact the design of future studies using RA in pre-clinical studies and guide preventive actions following genetic counselling and testing for children carriers of R337H germline mutation.…”
Section: Discussionsupporting
confidence: 66%
“…56 In addition, alterations in the retinoic acid pathway have also been linked recently to benign adrenocortical tumours secreting aldosterone. 57 In conclusion, our results offer human genetic evidence for the importance of the druggable RA pathway in ACC onset and extend its relevance to progression of both paediatric and adult ACC. These findings will impact the design of future studies using RA in pre-clinical studies and guide preventive actions following genetic counselling and testing for children carriers of R337H germline mutation.…”
Section: Discussionsupporting
confidence: 66%
“…Some years ago, proteomic analyses have suggested a role of retinoic acid receptor signaling in the early stage of adrenal development [88]. Invalidation of rar expression in mice results in structural disorganization of the adrenal cortex characterized by the loss of the radial organization of the ZF and abnormalities in vessel architecture and extracellular matrix, in both male and female mice, with no major modifications of aldosterone production [89]. Beyond the role of rar in the maintenance of the normal adrenal cortex structure and cell proliferation, dysregulation of this signaling may contribute to abnormal cell proliferation in PA [89].…”
Section: Animal Models Of Primary Aldosteronismmentioning
confidence: 99%
“…As the rate limiting step for aldosterone synthesis, CYP11B2 overexpression is present in a number of studies investigating gene expression profiles in APAs [ 14 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Interestingly, several studies have observed heterogeneity in CYP11B2 expression in APAs, with one subgroup overexpressed and another group with either unchanged or even reduced CYP11B2 expression [ 47 , 55 , 56 , 57 ]. Several studies confirmed that CYP11B2 expression was significantly higher in tumors carrying ATP1A1, ATP2B3 or CACNA1D mutations than in tumors carrying KCNJ5 mutations [ 47 , 48 , 49 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…In two older studies, however, lower DAX-1 expression was documented in APAs compared to cortisol-producing or non-functioning adrenal adenomas [ 54 , 64 ]. Finally, in a recent study, the nuclear receptor Retinoic Acid Receptor α, ( RARα ) showed significantly lower expression in APAs compared to normal adrenal glands; the nodulation occurring in APAs was attributed to its downregulation, as this molecule is responsible for normal adrenal zonation [ 55 ].…”
Section: Resultsmentioning
confidence: 99%